SOCIAL CONTRACT THEORY OF THOMAS HOBBES AND JEAN-JACQUES ROUSSEAU – UNITED OR OPPOSED? - Vojnović, Sava (Politeia, 2023)
Thomas Hobbes and Jean-Jacques Rousseau are among the most important modern political philosophers, who base their theories on the idea of social contract. Both authors start from the natural equality of all people and the uncertainty of the natural state, but at first glance they end up with completely different perspectives on sovereignty and relations within a political society. Rousseau insists on the common sovereignty of all citizens, who have a guaranteed economic minimum and the inalienable authority to enact laws and care for the general will, by which they all together simultaneously constitute those who are governed. Hobbes, on the other hand, dictates that the people elect a sovereign who is always in their natural state and must have great power in order to fulfil their role as protector. Yet, the paper argues that their positions are not really that different, bearing in mind Rousseau’s executive power and wise legislators, and Hobbes’ strong rights of subjects. The thesis of the paper is that in both of them the people authorize and supervise, and someone else rules.